Core concepts of accounting - Breitner, Leslie K.; Anthony, Robert N. (Boston : Prentice Hall, 2010)
For courses in Introductory Accounting This book is intended primarily for those who are studying, or who have completed, the programmed text Essentials of Accounting, 10/e. It contains the complete text of every point made in that book.
BSA
Keywords: Accounting